2012
DOI: 10.1080/10601325.2012.662059
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acrylic acid)-silicon Hybrids Prepared via a RAFT-mediated Process and Covalent Immobilization of Glucose Oxidase

Abstract: A surface modification technique was proposed for the modification of silicon surface with glucose oxidase (GOD). The silicon surface was first graft copolymerized with acrylic acid (AAc) via surface-initiated reversible addition-fragmentation chain-transfer (RAFT)-mediated process. With the aid of a water-soluble carbodiimide, GOD was then covalently immobilized on the silicon surface through the amide linkage between the amino group of GOD and the carboxyl group of the grafted AAc polymer. The changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In the case of inorganic–organic (hybrid), “hairy” particles, the thickness of the polymer brush shell affects the amount of immobilized enzyme as well. Gopalan et al presented polymer brush-based model systems composed of poly­(acrylic acid) or poly­(2-vinyl-4,4-dimethyl azlactone) and demonstrated, that the surface density of RNase increased linearly as the thickness of the brushes increased. , The same tendency was found by Shang et al, who also confirmed that the amount of covalently immobilized glucose oxidase increased with the increase in thickness of the grafted poly­(acrylic acid) . Further examples for this correlation were shown by the groups of Mao and Gao, who immobilized trypsin and lysozyme onto poly­(glycidyl methacrylate)-based brushes.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the case of inorganic–organic (hybrid), “hairy” particles, the thickness of the polymer brush shell affects the amount of immobilized enzyme as well. Gopalan et al presented polymer brush-based model systems composed of poly­(acrylic acid) or poly­(2-vinyl-4,4-dimethyl azlactone) and demonstrated, that the surface density of RNase increased linearly as the thickness of the brushes increased. , The same tendency was found by Shang et al, who also confirmed that the amount of covalently immobilized glucose oxidase increased with the increase in thickness of the grafted poly­(acrylic acid) . Further examples for this correlation were shown by the groups of Mao and Gao, who immobilized trypsin and lysozyme onto poly­(glycidyl methacrylate)-based brushes.…”
Section: Introductionmentioning
confidence: 71%
“…20,21 The same tendency was found by Shang et al, who also confirmed that the amount of covalently immobilized glucose oxidase increased with the increase in thickness of the grafted poly(acrylic acid). 22 Further examples for this correlation were shown by the groups of Mao 23 and Gao, 24 who immobilized trypsin and lysozyme onto poly-(glycidyl methacrylate)-based brushes.…”
Section: Introductionmentioning
confidence: 96%
“…Compared with conventional surfaces, a higher degree of biomolecule functionalization is achieved with P­(M)­AA brushes due to their 3D architecture and abundant carboxyl groups. Bovine serum albumin (BSA), , (strept)­avidin, , biotin, antigen/antibody, ,, acetylcholinesterase, ribonuclease A (RNase A), glucose oxidase, folic acid, , fluorescent protein, arginine-glycine-aspartic acid (RGD) peptide, ,, collagen, , galactose, ,, and silk sericin were successfully immobilized on P­(M)­AA brushes to impart different functionalities for various purposes, including biosensing, ,, catalysis, , targeting, , cell adhesion, and proliferation. ,,,,,,, …”
Section: Immobilization Of Biomoleculesmentioning
confidence: 99%
“…In the past decade, the hybrid nanoparticles composed of an inorganic core and a polymer shell have attracted great interest due to the intriguing properties associated with the nanohybrids, such as outstanding optical, mechanical, rheological, electrical, catalytic, and fire retardance (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%